Medication belief as correlate of medication adherence among patients with diabetes in Edo State, Nigeria - Olorunfemi, Olaolorunpo (Nurs Open, 2018)
AIM: The study aim was to determine the level of medication adherence, patient medication belief and to determine the correlation between medication belief and medication adherence among patients with diabetes. This is to find out whether medication belief of patient could enhance medication adherence which in turn would promote effective management of diabetic mellitus in Nigeria. BACKGROUND: The World Health Organization (WHO, 2015) estimated that over 366 million people are affected. The government and other non‐governmental organizations such as Diabetic Association of Nigeria (DAN) put several programmes in place to reduce the incidence of the disease, but minimal progress has been recorded, and the factors responsible for that is a big dilemma in the heart of researchers in the field. Empirical findings showed that, there is increased rate of re‐admission among DM patients and this is associated with poor medication adherence. There is a need to examine the factors responsible for poor medication adherence among patients with diabetes. In the review of the literature, medication belief is one of the major implicated factors, but there is no substantial evidence‐based research to validate this presumption in Nigeria. Therefore, this study is to find out the relationship between medication belief and medication adherence among patients with diabetes. DESIGN: A correlational research design was adopted, to enable the researcher in determining the association between the medication belief and medication adherence among patients with diabetes mellitus. METHODS: A total enumeration was adopted for the study, where all the registered adult patients were invited to join the study voluntarily and informed verbal consent was obtained, after explaining the importance of the study. A total of 180 patients with diabetes participated in the study. The Beliefs about Medicines Questionnaires (BMQ) and Morisky Medication Adherence Scale were used. This is a standardized scale and well validated with a reliability coefficient of 0.86, using split‐half model. A simple frequency distribution table and Spearman's rho correlational statistic were used to test the hypothesis at 0.05 level of significance. RESULTS: The data analysis shows that the clients had a negative perception about medication and believed that medication had the tendency of causing harm or poison to their system. The correlation between medication belief and medication adherence showed p = 0.005 which means that there is a statistical relationship between the two variables.